Neonatal Umbilical Myiasis - Our experience (Central Medical College Journal, 2022)
Background: Myiasis is an infestation of live vertebrates (humans and/or animals) by larvae of dipterous fly. Although, it usually infects domestic and wild animals but humans may be rarely affected if they are reared in unhygienic condition. Although adult cases have beenreported, neonatal myiasis is a rare condition and there are few reports aboutthis subject. Common sites of myiasisare exposed areas of the body such as extremities, scalp, and back. Herein, we report a case of umbilical myiasis, a 13days old neonate visited to outpatient department with complaint of worms coming out from umbilicus for 2 days. On examination, periumbilical erythema and umbilical discharge was present. The umbilical stump was irrigated with providine iodine, hydrogen per oxide and topical application with turpentine oil was given then worms were coming out from umbilicus. Umbilical myiasis is a very rare presentation indicating poor hygiene and a preventable condition.Central Medical College Journal Vol 5 No 1 Jan 2021 PP 59-62